Efficacy and Safety of Whey Protein Supplements on Vital Sign and Physical Performance Among Athletes: A Network Meta-Analysis - Lam, Fui-Ching; Bukhsh, Allah; Rehman, Habib; Waqas, Muhammad Khurram; Shahid, Nabeel; Khaliel, Adil Mohammed; Elhanish, Ahlam; Karoud, Mustfa; Telb, Ahmed; Khan, Tahir Mehmood (Frontiers in Pharmacology, 2019)
Introduction Athletes train physically to reach beyond their potential maximum aerobic threshold. Whey protein supplements (WPS) are often used in conjunction with physiotherapy and psychotherapy to regain better vital sign and physical performances. This review aimed to explore the clinical evidence on the efficacy and safety of WPS in sports performance and recovery among athletes. Methodology A comprehensive literature search was performed to identify relevant randomised control trials (RCTs) that investigated the efficacy and safety of WPS on vital sign and physical performance among athletes. The Cochrane Risk of Bias (ROB) Assessment tools was used to assess the quality of the studies. Meta-analysis was conducted using the frequentist model with STATA version 14.2®. Results A total of 333,257 research articles were identified out of which 20 RCTs were included for qualitative synthesis and network meta-analysis with 351 participants. Among the studies, 7 had low ROB and 3 RCTs had high ROB. In terms of the efficacy on vital sign outcome, the estimation efficacy of the supplements was generally similar to placebo. However, WPS significantly lowered rate of perceived exertion (WMD = -2.00; 95%CI -3.54,-0.46) compared to L-alanine. For the physical performance results of network meta-analysis demonstrated that WPS significantly increase average power by 112.00 watt (95% CI -187.91,-36.08) compared to carbohydrate, and WPS significantly decreased body mass by 6.89 kg (95% CI -8.24,-5.54). Conclusion The findings of this review supports the efficacy and safety of WPS as an ergogenic aid on athletes’ sports performance and recovery. The overall quality of clinical evidence was found to be valid and reliable from the comprehensive search strategy and ROB assessment.